2019
DOI: 10.1111/nep.13250
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cause of death between Australian and New Zealand Dialysis and Transplant Registry and the Australian National Death Index

Abstract: There is poor agreement in primary cause of death between ANZDATA and NDI which is in part explained by the absence of diabetes and renal failure as causes of death in ANZDATA and the absence of 'withdrawal' in NDI. These differences should be appreciated when interpreting epidemiological data on cause of death in the Australian end stage kidney disease population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…The reporting of cause of death in ANZDATA was reliant on the treating team and was not crossverified with the National Death Index. Prior comparison of the cause of death recorded in ANZDATA with the National Death Index has revealed good correlation for the timing of death, and fair agreement in the coding of cause of death, with the best agreement found for cancer-related deaths (28). There was also limited granularity of data collection and no information pertaining to transplant management protocols, changes in immunosuppression after transplant, or treatment adherence.…”
Section: Discussionmentioning
confidence: 99%
“…The reporting of cause of death in ANZDATA was reliant on the treating team and was not crossverified with the National Death Index. Prior comparison of the cause of death recorded in ANZDATA with the National Death Index has revealed good correlation for the timing of death, and fair agreement in the coding of cause of death, with the best agreement found for cancer-related deaths (28). There was also limited granularity of data collection and no information pertaining to transplant management protocols, changes in immunosuppression after transplant, or treatment adherence.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a population‐based cohort study of kidney transplant recipients using the Australian and New Zealand Dialysis and Transplantation Registry (ANZDATA). ANZDATA is a binational registry in operation since the inception of end‐stage kidney disease treatment in Australia and New Zealand, recording demographic, clinical and outcome data for all those in country receiving treatment …”
Section: Methodsmentioning
confidence: 99%
“…ANZDATA is a binational registry in operation since the inception of end-stage kidney disease treatment in Australia and New Zealand, recording demographic, clinical and outcome data for all those in country receiving treatment. 11 To determine the fact and cause of death, we linked ANZDATA with national death registers in Australia and New Zealand. In both countries', fact and cause of death reporting are mandatory.…”
Section: Study Cohortmentioning
confidence: 99%
“…12 Previous analyses have shown that cancer records within the ANZDATA Registry are robust and accurate, with a high concordance rate when compared with cancer incidence and mortality records reported to the New South Wales Cancer Registry 13 and the Australian National Death Index. 14 We included all cancer diagnoses and cancer deaths in adult patients (age 20 years old or older) except for nonmelanoma skin cancer, premalignant, or in situ lesions in our analyses. Date and causes of death as recorded in the ANZDATA Registry were also included.…”
Section: Ascertainment Of Cancer Deathmentioning
confidence: 99%